Dravsko polje (University of Maribor Press, 2023)
The Dravsko Polje Region. Until the mid of the 20th century, Dravsko polje (Drava field) was considered as a typical Pannonian rural landscape in northeastern Slovenia (between Maribor, Ptuj and Slovenska Bistrica), whose main identity was given by agrarian activities. With the process of urbanization and the development of other economic activities, such as industry, transport and the exploitation of the Drava River for hydropower, the character of the region began to change. As a result, Dravsko polje today represents a conflict zone of some contradictory or even mutually exclusive activities. The area gravitates towards three regional centers: Maribor, Ptuj and Slovenska Bistrica. Near each of these, the degree of transformation of settlements, modernization of spatial structures, or the degree of rurbanity is very high. The field is also one of most fertile regions in Slovenia. Recently, we have been emphasizing more and more often that to ensure self-sufficiency it is necessary to preserve arable land, but the actual development in the region is contrary to this axiom. We leave the best quality arable land to the expansion of built-up areas in the form of industrial plants, scattered individual construction and roads, but there is present also overgrowth of the highest quality areas for agriculture. In the monographic publication Dravsko polje, several authors in 12 chapters tried to shed light on some of current problems and processes in the region, which in recent decades has been marked by major changes and transformations, not only of natural but also of socioeconomic elements, while also paying attention to the area of regional interpretations for educational purposes.